Generation and characterisation of mesenchymal stem cell (msc)-like cells from induced pluripotent stem cells (ipscs) along with their co-culture effects on lung cancer cell line, h1975 - Loh, Jit Kai (2023)
Mesenchymal stem/stroma cells (MSCs) application in therapeutic treatment has increased attention, especially in regeneration, anti-inflammation, tumour suppression, and drug delivery treatments. However, the MSC interaction studies with tumours have shown both tumour-promoting and suppressing effects. One setback of MSC is the need for more homogenous supplies of cells for consistent treatment results and the limitation in obtaining large amounts of MSC cells from donors in a single extraction or culture expansion. To overcome this issue, induced pluripotent stem cells (iPSCs) technology has been used to derived MSCs (iMSC) that may provide alternative MSC sources for therapeutic treatment. In this study, iMSC was differentiated from peripheral blood mononuclear cell (PBMC)-derived iPSC. The generated 9iMSC was further characterised according to the International Society for Cell & Gene Therapy (ISCT) MSC 2005 guideline. Upon confirming its MSC-like properties and trilineage differentiation status, the iMSC was used to evaluate its inhibitory effects on H1975 lung cancer cells using an indirect co-culture approach involving either iMSC conditioned medium (iMSC-CM) treatment or iMSC transwell coculture (iMSC-TC) treatment. The effects of iMSC-CM on lung cancer cells demonstrated a significant increase in EMT-associated gene expression as compared to that of the parental cancer cells whereas no difference in EMT gene expression was observed between iMSC-TC treated cancer cells and that of the parental cancer cells. The migration assays also showed a high increase in migrated cells from H1975 cancer cells treated with iMSC-CM while H1975 cancer cells treated with iMSC-TC were similar to that of the control. Cytokine and chemokine assays revealed a number of releasing factors (CXCL1, CXCL12, GM-CSF, CCL2 and SDF-1) which were altered in the transwell coculture media when compared to the original culture media of iMSC and cancer cells alone. These observations indicated the effect of stroma microenvironment and cell-to-cell interaction by which the presence of both iMSC and H1975 cancer cells may influence the paracrine secretion profile of iMSC in its interaction with H1975 lung cancer cells resulting in suppression of its metastatic potential effects.